Living Qur’an in Action: The Practice of Ziyādah in Qur’anic Memorization among Students at UIN Syekh Wasil Kediri - Maula, Nabila An'imatul; Nur, Syafiqah; Mahmudah, Umi; Khairunnisa, Elvina; Umayyah, Asaa Nur Faridatul (Izzatuna: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
The phenomenon of ziyādah in Qur’anic memorization is generally associated with the community of ḥuffāẓ, those who have completed the memorization of the entire Qur’an. However, this study specifically highlights a similar practice undertaken by non-ḥuffāẓ students, a context that has been relatively underexplored within the field of living Qur’an studies. The research focuses on third-semester students of the Qur’anic Studies and Tafsir Program (IAT) at UIN Syekh Wasil Kediri. Its primary aim is to describe the forms of ziyādah implementation and to uncover the meanings embedded within the practice. Employing a qualitative descriptive approach with the living Qur’an method, data were collected through direct observation, in-depth interviews, and documentation of taḥfīẓ activities conducted in the academic environment. Findings reveal that ziyādah is routinely carried out in weekly taḥfīẓ sessions supervised by faculty members. Students participate not merely to increase memorization, but also to strengthen spirituality, enhance discipline, and internalize Qur’anic values in both academic and daily life. These results affirm that ziyādah among non-ḥuffāẓ students represents an authentic expression of religiosity, while simultaneously broadening the scope of living Qur’an practices within Islamic higher education. Abstrak Fenomena ziyādah hafalan Al-Qur’an umumnya identik dengan kalangan ḥuffāẓ, yaitu mereka yang telah menuntaskan hafalan secara menyeluruh. Namun, penelitian ini menyoroti praktik serupa yang dilakukan oleh mahasiswa non-ḥuffāẓ, sebuah konteks yang relatif jarang dikaji dalam ranah studi living qur’an. Fokus penelitian diarahkan pada mahasiswa Program Studi Ilmu Al-Qur’an dan Tafsir (IAT) semester III di UIN Syekh Wasil Kediri. Tujuan utamanya adalah mendeskripsikan bentuk pelaksanaan ziyādah serta menggali makna yang terkandung di balik praktik tersebut. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode Living Qur’an, di mana data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi kegiatan taḥfīẓ di lingkungan akademik. Hasil penelitian menunjukkan bahwa ziyādah dilaksanakan secara rutin dalam program taḥfīẓ mingguan yang dibimbing dosen pengampu. Mahasiswa mengikuti kegiatan ini bukan hanya untuk menambah hafalan, tetapi juga memperkuat spiritualitas, meningkatkan kedisiplinan, serta menginternalisasi nilai-nilai Qur’ani dalam aktivitas akademik maupun keseharian. Temuan ini menegaskan bahwa praktik ziyādah oleh mahasiswa non-ḥuffāẓ merupakan ekspresi keberagamaan yang otentik sekaligus memperluas cakupan makna Living Qur’an di perguruan tinggi Islam.